2021
DOI: 10.1177/03009858211066841
|View full text |Cite
|
Sign up to set email alerts
|

Chronological brain lesions after SARS-CoV-2 infection in hACE2-transgenic mice

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes respiratory disease, but it can also affect other organs including the central nervous system. Several animal models have been developed to address different key questions related to Coronavirus Disease 2019 (COVID-19). Wild-type mice are minimally susceptible to certain SARS-CoV-2 lineages (beta and gamma variants), whereas hACE2-transgenic mice succumb to SARS-CoV-2 and develop a fatal neurological disease. In this article, we aimed to chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 55 publications
11
65
5
Order By: Relevance
“…Mice are not naturally sensitive to SARS-CoV-2 replication, but transgenic expression of human ACE2 or transduction of mice with adenovirus or adeno-associated viruses expressing human ACE2 sensitizes mice to SARS-CoV-2 infection. Although the tissue and cell ACE2 expression in these models differs from that in humans, these mice models have been used to study the effect of both virus replication [79][80][81][82] and inflammation-induced changes [73,83,84] in the brain. Although the observations cannot be extrapolated directly to humans, they provide important insights into the different mechanisms that could contribute to the large spectrum of neurological complications following SARS-CoV-2 infection.…”
Section: Models and Techniques To Study The Neuroinvasiveness Neurotr...mentioning
confidence: 99%
“…Mice are not naturally sensitive to SARS-CoV-2 replication, but transgenic expression of human ACE2 or transduction of mice with adenovirus or adeno-associated viruses expressing human ACE2 sensitizes mice to SARS-CoV-2 infection. Although the tissue and cell ACE2 expression in these models differs from that in humans, these mice models have been used to study the effect of both virus replication [79][80][81][82] and inflammation-induced changes [73,83,84] in the brain. Although the observations cannot be extrapolated directly to humans, they provide important insights into the different mechanisms that could contribute to the large spectrum of neurological complications following SARS-CoV-2 infection.…”
Section: Models and Techniques To Study The Neuroinvasiveness Neurotr...mentioning
confidence: 99%
“…Early reports communicated lethality to be associated primarily with severe lung inflammation and impaired respiratory function, suggesting that the K18-hACE2 model recapitulates features of the respiratory disease observed in severe cases of COVID-19 diagnosed with ARDS [ 28 , 36 ]. However, the confounding impact of neuroinvasion and neurodissemination and its role in the clinical decline of SARS-CoV-2 infected K18-hACE2 mice is becoming more readily acknowledged [ 41 , 42 , 43 , 44 ]. Furthermore, administration of aerosolized SARS-CoV-2 to K18-hACE2 mice resulted solely in respiratory infection and limited clinical disease at 6 days post infection (6 dpi) in contrast with those inoculated intranasally, suggesting that severe clinical outcome in K18-hACE2 mice is attributed to CNS disease [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal death via apoptosis was suspected [44]. Other studies reported perivascular cuffs or vasculitis, neuronal degeneration and necrosis, satellitosis, parenchymal edema, and occasional mi-crothrombi [42,45,5456], all at day 7 pi. The present study confirms that SARS-CoV-2 variants readily infect neurons in the K18-hACE2 mice, with viral protein accumulation in the entire cytoplasm including the cell processes but does not provide evidence of neu-ronal cell death in association with infection, indicating that SARS-CoV-2 has no direct cytopathic effect on neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia may itself undergo a phenotypic shift and display exaggerated release of proinflammatory mediators and aberrant phagocytic activity, inducing neurodegeneration [64]. This could explain the diffuse astrogliosis reported from other mouse and human studies [9,42,45] as well as neuronophagia by microglial cells which was seen in some human COVID-19 patients [23] and one mouse study [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation